Lasunadi Agada in Lootha Visha Chikitsa - A Review (International Journal of Ayurveda and Pharma Research, 2023)
Agadatantra had a golden time period in Kerala, and was known in the name of Visha chikitsa. There were excellent Visha vaidhyas who used to treat extreme venomous conditions and even predict the condition of patient just through the Dootha lakshana. As a part of these practices, there were numerous textbooks on Visha chikitsa with unique and exclusive Yogas. Some of the books got maintained, and many got ruined. Among those only few practices are still in use in the management if Visha and still many are untouched. Prayoga samucchaya is a well-known traditional Keraleeya Visha chikitsa textbook written by renowned King Kochunni thamburan, which explains the concepts of Visha and its detail management. Lootha visha is a most frequent and important clinical condition that which a physician encounters in their daily practice. It has got importance in all the time, as its manifestation is in such a way that improper handling of the case may worsen the presentation. There many Agada yogas mentioned in the management of Lootha visha. Lasunadi Agada is a simple yoga explained in Prayoga samucchaya, which contains only 6 drugs, explained in the context of Lootha samanya chikitsa as Pana and Nasya. Presently this yoga is practicing in the name of Lasunadi gulika. So this paper is an attempt to review on the formulation Lasunadi Agada.